2004
DOI: 10.1093/jxb/erh167
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of growth and nitrogen uptake to organic nitrogen in four gramineous crops

Abstract: The capability to utilize different forms of nitrogen (N) by sorghum (Sorghum bicolor), rice (Oryza sativa), maize (Zea mays), and pearl millet (Pennisetum glaucum) was determined in pot experiments. Seedlings were grown for 21 d without N, or with 500 mg N kg(-1) soil applied as ammonium nitrate, rice bran or a mixture of rice bran and straw. No treatment-dependent changes of root length, surface area, and fractal dimension were observed. Shoot growth and N uptake in maize and pearl millet correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…The high contribution of plant-induced solubilization to N uptake has also been reported at least for white lupin (Watanabe et al, 2006), sorghum (Okamoto et al, 2004) and F. vivipara (a grass growing in sub-arctic montane in north Sweden) (Jonasson et al, 2006). In these studies, both planted and unplanted soils were examined, by which the contribution of solubilization by the plant could be estimated in a way similar to ours.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The high contribution of plant-induced solubilization to N uptake has also been reported at least for white lupin (Watanabe et al, 2006), sorghum (Okamoto et al, 2004) and F. vivipara (a grass growing in sub-arctic montane in north Sweden) (Jonasson et al, 2006). In these studies, both planted and unplanted soils were examined, by which the contribution of solubilization by the plant could be estimated in a way similar to ours.…”
Section: Discussionsupporting
confidence: 69%
“…Bars with * and + indicate significant differences between the planted and unplanted treatments at the level of P<0.05 and P<0.1, respectively (t-test). Okada, 2004;Watanabe et al, 2006). The concentration of inorganic N in soil planted with F. vivipara became higher than that in the unplanted soil in half of the treatments (Jonasson et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the level of proteolytic activity in the culture medium of different plant species varied significantly (Godlewski and Adamczyk, 2007). Also the uptake of amino acids -the product of proteolysis process -differs between various plant species (weigelt et al, 2003okamoto and Okada, 2004;Reeve et al, 2009).…”
mentioning
confidence: 99%
“…Moreover, Näsholm et al [53] showed the ability of five important crop species (Phleum pretense, Ranunculus acris, Trifolium hybridum, Trifolium pretense and Triticum aestivum) to take up the amino acid glycine [53,54]. Even proteins can be used by some plant species (Sorghum bicolor and Oryza sativa), as demonstrated by Okamoto and Okada [55]. They found that these two species possess high capabilities for taking up protein, which could be important when they are cultivated in low inorganic N concentrations.…”
Section: Carnivorous Plantsmentioning
confidence: 99%